2000
DOI: 10.1074/jbc.275.4.2390
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Activation of Calpain Is Required for Fibroblast Motility and Occurs via an ERK/MAP Kinase Signaling Pathway

Abstract: To become migratory, cells must reorganize their connections to the substratum, and during locomotion they must break rear attachments. The molecular and biochemical mechanisms underlying these biophysical processes are unknown. Recent studies have implicated both extracellular signal-regulated kinase/mitogen-activated protein (ERK/MAP) kinase and calpain (EC 3.4.22.17) in these processes, but it is uncertain whether these are two distinct pathways acting on different modes of motility. We report that cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
260
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(272 citation statements)
references
References 44 publications
(58 reference statements)
6
260
2
Order By: Relevance
“…Indeed, Zaidel-Bar , 2007 et al recent studies have demonstrated that the calpain family has a regulatory function in cell motility, partly through the capacity to down regulate integrin-mediated adhesion complexes ( ; ; ; ). In that Glading , 2000et al Dourdin , 2001et al Bhatt , 2002et al Glading , 2002 context, talin seems to be one of major target of calpain leading to a rate-limiting step critical for FA disassembly ( ). It Franco , 2004 et al has also been shown that the expression of a calpain-resistent cortactin impaired cell migration and increased transient membrane…”
Section: Disassembly Of Cell-matrix Adhesionsmentioning
confidence: 99%
“…Indeed, Zaidel-Bar , 2007 et al recent studies have demonstrated that the calpain family has a regulatory function in cell motility, partly through the capacity to down regulate integrin-mediated adhesion complexes ( ; ; ; ). In that Glading , 2000et al Dourdin , 2001et al Bhatt , 2002et al Glading , 2002 context, talin seems to be one of major target of calpain leading to a rate-limiting step critical for FA disassembly ( ). It Franco , 2004 et al has also been shown that the expression of a calpain-resistent cortactin impaired cell migration and increased transient membrane…”
Section: Disassembly Of Cell-matrix Adhesionsmentioning
confidence: 99%
“…Calpain cleavage of talin here is a rate limiting step in disassembly of other focal adhesion components including zyxin, paxillin and vinculin [190]. Recent studies have demonstrated that growth factor stimulation of calpain activity and cellular deadhesion is dependent upon ERK [191,192]. Calpain is directly phosphorylated by ERK in response to EGF stimulation and this increases calpain's proteolytic activity [96].…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…Indeed, calpain may be one of the "relaxing" factors targeted to focal adhesions by microtubules for focal adhesion disassembly [140]. Src [200], FAK and MEKK1 [193] appear to regulate calpain activity in part through ERK phosphorylation of the protease [96,192]. FAK null cells exhibit less stable microtubules [201], lower calpain activity [193], decreased ERK signaling [198,202,203] and reduced migratory potential due to defects in focal adhesion disassembly [86], consistent with the view that signaling from FAK to ERK may alter migratory responses through ERK stimulated calpain proteolysis of focal adhesion components and actin remodeling, and microtubule dynamics.…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…28 Therefore, we utilized an Figure 6 Capn4 silencing and overexpression of calpastatin correlate with increased p50 and p105 protein levels in vivo. Panel a: Capn4 siRNA or control siRNA were transfected in the indicated cell lines.…”
Section: Capn4à/à Mefs Are Defective In Nf-jb Regulation By C2 Ceramidementioning
confidence: 99%
“…Binding of ligand to EGFR was shown to lead to activation of milli-calpain subsequent to ERK/MAP kinase signalling. 28,29 Endoplasmic reticulum (ER) stress-inducing agents such as thapsigargin, ionomycin and ceramides are widely used as triggers of calpain activity 27 to elucidate the molecular events underlying calpain-involved signalling.…”
Section: Introductionmentioning
confidence: 99%